2012
DOI: 10.4314/tjpr.v11i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Standardized Decoction of <i>Nigella sativa</i> Seed, <i>Hemidesmus indicus</i> Root and <i>Smilax glabra Rhizome on the Expression of p53 and p21 Genes in Human Hepatoma Cells (HepG2) and Mouse Liver with Chemically-Induced Hepatocarcinogenesis

Abstract: Purpose: To evaluate in vitro (using human hepatoma HepG2 cells) and in vivo (using mouse liver with diethlynitrosamine (DEN)-induced hepatocarcinogenesis) effect of a standardized decoction on the expression of p53 (tumour suppressor) and p21 (cyclin kinase inhibitor) genes with the long-term goal of developing the formulation into a globally acceptable therapy for hepatocellular carcinoma (HCC). Methods: The effect of the decoction on (a) mRNA and (b) protein expression of p53 and p21 genes in HepG2 cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Previous in vivo and in vitro investigations [ 1 , 2 ] have shown that the decoction, comprised of N. sativa seed, H. indicus root, and S. glabra , can mediate anti-hepatocarcinogenic effects, without producing any significant toxic side effects. The antihepatocarcinogenic effects of the decoction probably results from an impact of this polyherbal formulation on a broad range of biochemical activities including antioxidant activity [ 5 ], anti-inflammatory activity, immunomodulatory activity and modulation of activities of factors involved in cell proliferation and cell cycle arrest [ 3 , 4 , 6 ]. In the study carried out by Thabrew et al , (2005), a flow cytometric analysis of HepG2 cells exposed to the test decoction indicated that this polyherbal formulation also has the potential to induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vivo and in vitro investigations [ 1 , 2 ] have shown that the decoction, comprised of N. sativa seed, H. indicus root, and S. glabra , can mediate anti-hepatocarcinogenic effects, without producing any significant toxic side effects. The antihepatocarcinogenic effects of the decoction probably results from an impact of this polyherbal formulation on a broad range of biochemical activities including antioxidant activity [ 5 ], anti-inflammatory activity, immunomodulatory activity and modulation of activities of factors involved in cell proliferation and cell cycle arrest [ 3 , 4 , 6 ]. In the study carried out by Thabrew et al , (2005), a flow cytometric analysis of HepG2 cells exposed to the test decoction indicated that this polyherbal formulation also has the potential to induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The decoction has been standardized considering its High Performance Liquid Chromatography (HPLC) profile and physico-chemical parameters according to WHO guidelines [ 3 ]. Further in vivo and in vitro investigations have demonstrated that cytotoxicity, [ 3 , 4 ] antioxidant activity, anti-inflammatory activity [ 5 ] and up regulation of p53 and p21 activities [ 6 ] are some of the possible mechanisms through which the above decoction may mediate its anti-hepatocarcinogenic action.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory cell pellets were lysed in RIPA buffer ( 50 mM Tris-HCl (pH 7.6), 150 mM NaCl, 1 % NP-40, 0.5 % sodium deoxycholate, 0.1 % SDS) [17] and EDTA-free protease inhibitor cocktail (Roche, Basel, Switzerland). Equal amounts of protein samples were separated by SDS-PAGE electrophoresis and transferred onto PVDF membranes (Milipore, MA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…There is no beneficial cure for this malignancy [ 10 ] and the recovery rate of HCC is low in most cases [ 11 ]. In addition, the inevitable side effects, such as toxicity to normal cells and bone marrow illustrate an instant demand to search for better methods and novel anti-cancer agents that would decrease the mortality rate of HCC with fewer side effects [ 12 ].…”
Section: Introductionmentioning
confidence: 99%